2019
DOI: 10.1002/ece3.5378
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association analyses reveal polygenic genomic architecture underlying divergent shell morphology in SpanishLittorina saxatilisecotypes

Abstract: Gene flow between diverging populations experiencing dissimilar ecological conditions can theoretically constrain adaptive evolution. To minimize the effect of gene flow, alleles underlying traits essential for local adaptation are predicted to be located in linked genome regions with reduced recombination. Local reduction in gene flow caused by selection is expected to produce elevated divergence in these regions. The highly divergent crab‐adapted and wave‐adapted ecotypes of the marine snail Littorina saxati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 90 publications
(133 reference statements)
0
27
0
Order By: Relevance
“…Another recent GWA study using SNP loci called without a reference genome (Kess & Boulding, 2019) also found genome‐wide trait association signals across regions of varying levels of differentiation, but higher overall ecotype divergence among trait‐associated loci. However, here we uncover greater enrichment of trait‐associated loci in genomic regions with putative rearrangements compared with Kess and Boulding (2019).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Another recent GWA study using SNP loci called without a reference genome (Kess & Boulding, 2019) also found genome‐wide trait association signals across regions of varying levels of differentiation, but higher overall ecotype divergence among trait‐associated loci. However, here we uncover greater enrichment of trait‐associated loci in genomic regions with putative rearrangements compared with Kess and Boulding (2019).…”
Section: Discussionmentioning
confidence: 92%
“…However, here we uncover greater enrichment of trait‐associated loci in genomic regions with putative rearrangements compared with Kess and Boulding (2019). Previous genome‐wide association analyses with this morphometric data set (Kess & Boulding, 2019) used aligned shell landmark coordinates in addition to relative warps and did not include shell ornamentation traits. Many individual landmark coordinates in Kess and Boulding (2019) likely did not covary with ecotype, and therefore, many loci identified would not be expected to overlap with rearrangement regions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations